Impact of POR and CYP3A5 Polymorphisms on Trough Concentration to Dose Ratio of Tacrolimus in the Early Post-operative Period Following Kidney Transplantation. Issue 5 (October 2018) - Phupradit, Annop; Vadcharavivad, Somratai; Ingsathit, Atiporn; Kantachuvesiri, Surasak; Areepium, Nutthada; Sra-ium, Supasil; Auamnoy, Titinun; Sukasem, Chonlaphat; Sumethkul, Vasant; Kitiyakara, Chagriya
Abstract : Background: Tacrolimus, a critical dose drug, is widely used in transplantation. Knowing the contribution of genetic factors, which significantly influence tacrolimus variability, is beneficial in the personalization of its starting dose. The significant impact of CYP3A5*3 polymorphisms on tacrolimus exposure has been reported. Conflicting results of the additional influence of POR*28 polymorphisms on tacrolimus pharmacokinetic interindividual variability have been observed among different populations. The objective of this study was to explore the interaction between POR*28 and CYP3A5*3 polymorphisms and their main effects on tacrolimus trough concentration to dose ratios on day 7 after kidney transplantation. Methods: Two hundred sixteen adult kidney transplant recipients participated in this retrospective study. All participants received a twice daily tacrolimus regimen. Blood samples and data were collected on day 7 after transplantation. A 2-way analysis of covariance was performed. Tested covariates were age, hemoglobin, serum albumin, and prednisolone dose. Results: A 2 × 2 analysis of covariance revealed that the interaction between CYP3A5 polymorphisms (CYP3A5 expresser and CYP3A5 nonexpresser) and POR polymorphisms ( POR*28 carrier and POR*28 noncarrier) was not significant ( F (1, 209) = 2.473, P = 0.117, = 0.012). The predicted main effect of CYP3A5 and POR polymorphisms was significant ( F (1, 209) = 105.565, P < 0.001, = 0.336 and F (1, 209) = 4.007, P = 0.047, = 0.019, respectively). Hemoglobin, age, and steroid dose influenced log C0 /dose of tacrolimus ( F (1, 209) = 20.612, P < 0.001, = 0.090; F (1, 209) = 14.360, P < 0.001, = 0.064; and F (1, 209) = 5.512, P = 0.020, = 0.026, respectively). Conclusions: After adjusting for the influences of hemoglobin, age, and prednisolone dose, significant impacts of the CYP3A5 and POR polymorphisms on tacrolimus exposure were found. The effect of POR*28 and CYP3A5*3 polymorphisms during the very early period after kidney transplantation is independent of each other.